Analysis of Inequality of Income Distribution in North Sumatra in 2011-2022 - Salimah, Nur; Waruwu, Asro Felix; Naibaho, Cindy Yentika; Dongoran, Faisal Rahman (PT. Riset Press International, 2023)
In a country, both developing and developed countries, the problem that often occurs is economic problems or income distribution that is not evenly distributed in all corners of the country. Indonesia is no exception, especially in the province of North Sumatra. The research method that the author uses is descriptive research method, namely the research results are obtained from accurate and clear secondary data sourced from Gini coefficient data and the Central Bureau of Statistics (BPS). From the results of observations or data results obtained that the result of unequal income distribution in Indonesia has resulted in social inequality, poverty and income inequality. The effect of income inequality is that money causes the rich to get richer and the poor to get poorer. As a result, many new problems arise from the income inequality effect. The purpose of this study was to determine the inequality of income distribution in North Sumatra from 2011 to 2022. The conclusion obtained from income distribution data in the North Sumatra region is that income inequality in this region has increased from 2011 to 2022.